Congenital Uterovaginal Prolapse in a Newborn - Zenebe Wolde Jijo; Million Teshome Betele; Abdurazak Shemolo Ali (Hindawi Limited, 2018)
Background. Uterovaginal prolapse is a rare condition in newborns which is usually associated with spinal cord defects. It is usually diagnosed at birth. Different treatment options have been proposed for genital prolapse in newborns. Most of the treatment options recommended are conservative; radical approach is rarely suggested for the treatment of these cases. Case Details. We report a 6-hour-old newborn that was diagnosed to have congenital uterovaginal prolapse and was successfully managed conservatively with digital reduction of the mass and strapping of both legs together. Conclusion. Congenital uterovaginal prolapse in newborns can be managed conservatively with simple digital reduction followed by strapping of the legs together; this approach is simple and cost-effective and has no associated complications.